Investigating the intelligence of investors of mutual funds during the recession and economic prosperity of the capital market - Bahreh Heidarimoghadam; Mirfeiz Fallahshams; Gholamreza Zomorodian (راهبرد مدیریت مالی)
The purpose of this study is to investigate the ability of mutual fund investors to predict the performance of mutual funds and select a fund with higher returns. To predict whether investors and the cash they enter into investment funds will be able to select a more efficient fund, first, the information of 34 funds in the period 2012 to 2020 was Collected to examine the intelligence of cash. The economic prosperity periods of the market were then examined separately to determine whether investors had acted differently in different market periods. Also, real and legal investors are separated from each other to examine the performance of each separately. Using Carhart's four-factor model, the adjusted return on risk of the funds was calculated to assess the intelligence of investors, which showed that group of real and legal investors, at the time of entry during market blooming and at the time of exit money during market stagnation act wisely in mutual funds.